2004
DOI: 10.1007/s00330-004-2351-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of preoperative MRI of the breasts on recurrence rate in patients with breast cancer

Abstract: Preoperative MRI of the breasts has been proven to be the most sensitive imaging modality in the detection of multifocal or multicentric tumor manifestations as well as simultaneous contralateral breast cancer. The aim of the presented retrospective study was to evaluate the benefit of preoperative MRI for patients with breast cancer. Preoperative MRI performed in 121 patients (group A) were compared to 225 patients without preoperative MRI (group B). Patients of group A underwent contrast-enhanced MR imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(135 citation statements)
references
References 30 publications
2
121
0
12
Order By: Relevance
“…This may be of particular concern in younger patients where the local recurrence rate is approximately twice as large as in older patients. In a retrospective analysis, Fisher and colleagues reported that preoperative MRI reduced the incidence of local recurrence [36]. Impact of preoperative MRI on surgical precision was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…This may be of particular concern in younger patients where the local recurrence rate is approximately twice as large as in older patients. In a retrospective analysis, Fisher and colleagues reported that preoperative MRI reduced the incidence of local recurrence [36]. Impact of preoperative MRI on surgical precision was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Although how much this extends into clinical and long term survival benefit is still a matter of debate. Clinical trials exist for both invasive and in situ carcinoma in which no significant difference in survival was found in patients treated with BCT or mastectomy [24][25][26]. Both radiation therapy and adjuvant systemic chemotherapy contribute to low rates of cancer recurrence in treated breast.…”
Section: Detection Of Additional Lesions On Mri With or Without Non Mmentioning
confidence: 99%
“…The clinical significance of detecting these additional sites of disease was reported by a German group in a retrospective review of 346 patients who were preoperatively staged with (n=121) or without (n=225) MRI (23). At a mean follow-up of 40 months, the in-breast tumour recurrence rate in patients treated with breast conservative therapy and staged with MRI was 1.2% (1/86) compared with 6.5% (9/138) of the patients staged without preoperative MRI (P<0.001).…”
Section: Mri and Other Imaging Modalitiesmentioning
confidence: 99%